The effect of carbon on the electronic structure of FeNi alloys with a stacking fault - Jasen, Paula Verónica (2008)
The bonding of C to Fe and Ni in Fe50Ni50(L1 0) alloy with a stacking fault (SF) is analyzed using density runctional calculations (DFT). The changes in the electronic structure of the bulk alloy upon SF introduction and after C absorption is addressed. C locates in an octahedral site with Ni atoms in its base and capped with Fe atoms. The Fe-Ni and Ni-Ni bonding decrease while the Fe-Fe bonding increases when the SP is introduced. The effect of C is to reduce the Pe-Ni and Ni-Ni overlap population (OP) up to 75% of its original value, while the Fe-Fe OP only changes by 3.6%, Both Fe and Ni bond to C atom at a distance of 1.80 Å, which is close to that in Fe and Ni carbides metallic, clusters or C as a impurity at grain boundaries or dislocations. © 2008 WILEY-VCH Verlag GmbH & Co. KGaA.